New bael varieties for dryland - Singh, A K; Singh, Sanjay; Singh, R S; Sharma, B D; Saroj, P L (Indian Horticulture, 2023)
Three new abiotic stress tolerant varieties (Thar Srishti, Thar Prakriti and Thar Shivangi) of bael have been developed by Central Horticultural Experiment Station (ICAR-CIAH), Godhra, Gujarat. These varieties perform well in abiotic stress conditions, and have been identified at institute level for specific traits like Thar Srishti for highly centric locule arrangement, Thar Prakriti for high fibre and papery shell (1.4 cm) and Thar Shivangi for high antioxidant activity having drooping branches. Economic yield from full grown tree can be obtained up to 400 mm rainfall under rainfed hot semi-arid conditions of western India. These varieties were evaluated purely under hot rainfed semi-arid conditions and have been recommended for commercial cultivation under dryland areas of country.